Enterprise Architecture Design Using TOGAF ADM: The Case of KotaKita - Prawira, Dimas Yudha; Kurniawan, Rido Dwi; Indrajit, Richardus Eko; Dazki, Erick (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
One of the benefits of implementing enterprise architecture is creating harmony in between business and information technology for the needs of organization, beside that information system architecture is also a management practice and technology that is useful to improve company performance by allowing them to see themselves in terms of a holistic and integrated view of strategic direction, business practices, information flows and technological resources (Wiranti et al., 2020). The application of enterprise architecture is inseparable from how to plan an organization but also in designing enterprise architecture. In carrying out the design required a complete and easy methodology. TOGAF (The Open Group Architecture Framework) as a framework for building generic enterprise architectures provides complete and easy-to-understand and implement stages. Currently there are not many applications or systems that provides local city information, communication and social media (events, tourist sites, business listings, communities, so on and so forth). Although there is, the application or system does not provide information in an informative manner, the information is scattered in various sources. KotaKita is a product which will be build by startup organization to fill the gap and providing the information on the locality of areas throughout Indonesia, KotaKita can be used as a means of communication of local regional social communities. The Implementation of enterprise architecture (EA) in startup organizations is not a must, but the implementation of enterprise architecture will be very useful in building an architectural blueprint that can be used to make better plans and decisions.